THE DEFINITION OF MATERIAL DEFORMATION STRENGTHENING IN THE VOLUME OF INDIVIDUAL GRAINS OF POLYCRYSTALS - Vakulenko, L. I.; Gryshchenko, M. A. (Science and Transport Progress, 2008)
The questions of microhardness estimate in changing the loading on indenter, if the same place of a sample is loaded, are considered.